The Butterfly-Shaped Feedback Loop in Networked Control Systems for the Unknown Delay Compensation - Lai, Chien-Liang; Hsu, Pau-Lo (My University, 2014)
Available model-based networked control system (NCS) design approaches are basically formulated from the known system model and the information of the networked-induced delay time. Because the delay in remote control systems is significant and time-varied as commercial networks involved, available model-based NCS design approaches may thus become impractical. The increase of time delay due to the limited communication bandwidth usually induces data dropout to make NCS design even more difficult. In this paper, the scheme of the perfect delay compensation (PDC) is proposed by introducing the butterfly-shaped inner feedback loop in NCS to deal with the unknown network-induced time delay. Furthermore, analytical results indicate that the controller obtained in general control systems can be directly implemented on NCS with the proposed PDC scheme. Both simulation and experimental results were successfully carried out on an ac servo motor at a distance of 15 km through Ethernet to maintain a stable remote control system.
Keywords: Butterfly element; delay compensation; implementation; networked control systems (NCS); network-induced delay